Effectiveness of co-amoxiclav antibiotic therapy in carbuncle patients with type II diabetes mellitus - Saputri, Dian Mahfudz Asri (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Carbuncle is a confluent folliculitis that is infection affecting multiple hair follicles leading to multiple sinuses discharging pus. Optimisation of co-morbidities such as diabetes, adequate hydration, and antibiotics and are mainstay of initial treatment. Surgical intervention in the form of debridement and desloughing followed by wound care is the next line of management. The aim of this study was to know the effectiveness of co-amoxiclav antibiotic therapy in carbuncle patients with type II diabetes mellitus at the Surgical Polyclinic of Sabu Raijua Regional Hospital. Methods: This type of research is quantitative research using a cross-sectional retrospective approach. The sample in this study was patient data collection through medical records from 2023 to 2024 who underwent co-amoxiclav therapy of 1000 mg every 8 hours orally for 10 days accompanied by incision drainage with local anesthesia of 2% lidocaine with a carbuncle size of >10 cm who were treated at the Surgical Polyclinic of Sabu Raijua Hospital, totaling 10 patients. Findings: The results of therapy with co-amoxiclav antibiotic 1000 mg every 8 hours orally for 10 days accompanied by incision drainage with local anesthesia lidocaine 2% with carbuncle size >10 cm who received treatment were 10 patients who successfully recovered with outpatient care, did not experience complications or readmissions. Conclusion: In early-stage carbuncle cases, treatment with oral co-amoxiclav antibiotics alone is possible and effective, although incision and drainage should still be performed as early as possible. Novelty/Originality of this Article: This study demonstrates the effectiveness of the combination of oral co-amoxiclav 1000 mg/8 hours for 10 days with incision-drainage in carbuncles >10 cm with type II DM, which can be successfully treated as an outpatient without complications or readmissions.